Differential Regulation Of Peroxisome Proliferator Activated Receptor Gamma (Ppary) By Cytokines In Murine Macrophage J774.2 Cell Line : Elucidation Of Signal Transduction Pathways Of Tumour Necrosis Factor Alpha (Tnfa) In Regulating Macrophage Ppary Gene Expression [QH603.P47 L732 2007 f rb]. - Lim, Chui Hun (2007)
Aterosklerosis merupakan punca kematian utama di negara-negara maju. Peranan PPARγ dalam makrofaj yang diaktifkan oleh sitokina adalah penting di dalam patogenesis aterosklerosis.